Pengembangan Team-Based Collaboration untuk Kinerja Operasional Petani Dusun Butuh, Kecamatan Sumowono - Ahmad Ali; Rahmania Argita Dwijayanti; Isra Prihantini; Renita Ayu Listiyani; Muhammad Ma'Ruf Saifullah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aims to improve the operational performance and distribution of the Sido Subur Farmers Group in Butuh Hamlet, which faces challenges such as difficulty finding suppliers, low crop prices, and plant virus attacks such as the yellow virus on chilies and Patek. This program was chosen as a solution to strengthen farmers' capacity through teamwork-based learning and training with a healthy competitive approach. Implementation methods included workshops, group discussions, and hands-on field practice related to crop management and distribution strategies. The results demonstrated an increase in farmers' understanding and skills in managing their farms, marketing their crops, and building innovation through more effective collaboration. This program is important because it increases the efficiency of farmer groups, strengthens solidarity among members, and supports sustainable community welfare.